Studies on Production, Optimization and Purification of Uricase from Gliocladium viride - Nanda, Pooja; Babu, P.E. Jagadeesh; Fernandes, Jenifer; Hazarika, Pranita; Dhabre, Rohini Raju (Research in Biotechnology, 2012)
Five different fungal strains belonging to Gliocladium and Gliomastix species were initially screened for their uricase producing capability, among which Gliocladium viride MTCC 3835 was identified to produce highly active uricase. Statistical designs were applied to optimize uricase production. Using PlackettÃ¢â‚¬â€œBurman design, peptone, yeast extract and CuSO4 were found to have significant effect on enzyme activity. Box-Behnken design was used to find the optimal concentrations of significant variables, which were as follows, Peptone-12.71g/L, Yeast Extract-10.57g/L,Ã‚Â CuSO4-0.0762g/L. Maximum activity of 84.92 U/ml was observedÃ‚Â experimentally, which is 1.344 times higher than the activity got in basal medium. Crude uricase was further purified using three-phase partitioning (TPP), and the significant factors like inorganic phase saturation, ratio between organic phase and crude enzyme, operating temperature were optimized. Crude enzyme saturated with 50%(w/v) with ammonium sulphate and at crude enzyme to t-butanol ratio of 1:1(v/v) at 30Ã‚Â°CÃ‚Â resulted in 80.109% yield of uricase with 1.44 fold purification.